قلق الموت وعلاقته بالأمن النفسي: دراسة ميدانية لدى عينة من طلبة كلية التربية في جامعة دمشق - العمر، محمد محمد صابر; نحيلي، علي أحمد عبدالله (جامعة البعث, 2016)
This research aims at present to detective level of death anxiety and Emotional Security among sample of research, and the correlation between Self-assurance and its relationship to Emotional Security, as well as to detect differences between the average scores students at the scale death anxiety and Emotional Security among faculty members according to the following change (study of year) among the students of the faculty of education. To achieve this goal has been to use the following tools: Questionnaire to measure the of Emotional Security the preparation alawad, 2013. And a questionnaire to measure of death anxiety of the preparation of researcher. The study sample consists of (463) male and female students from Damascus university. The most important findings of Search: -Level of death anxiety was Low. -Level of Emotional Security was high. -There are correlation statistically significant negative between the scores of students on a scale of death anxiety and grades on a scale of to Emotional Security. -There are differences between the mean scores of students on a scale of death anxiety due to the variable study of year favor first year. -There are differences between the mean scores of students on a scale of Emotional Security due to the variable specialization of academic favor four year.
هدف البحث التعرف إلى مستوى كل من قلق الموت والأمن النفسي لدى أفراد عينة البحث وتعرف العلاقة الارتباطية بين قلق الموت والأمن النفسي، ومعرفة الفروق بين متوسط درجات الطلبة أفراد عينة البحث على مقياس قلق الموت والأمن النفسي تبعا لمتغير السنة الدراسية. تكونت عينة البحث من (463) طالبا وطالبه من طلبة كلية التربية بجامعة دمشق، وطبق عليهم مقياس قلق الموت من إعداد الباحث ومقياس الأمن النفسي من إعداد (العوض 2013) وذلك بعد التحقق من صدقهما وثباتهما. وأشارت النتائج إلى ما يلي: — انخفاض مستوى قلق الموت لدى أفراد عينة البحث. — ارتفاع مستوى الأمن النفسي لدى أفراد عينة البحث. — وجود علاقة ارتباطيه سالبة ذات دلالة إحصائية بين درجات الطلبة أفراد عينة البحث على مقياس قلق الموت ودرجاتهم على مقياس الأمن النفسي. — وجود فروق بين متوسط درجات أفراد عينة البحث على مقياس قلق الموت لصالح طلبة السنة الأولى. — وجود فروق بين متوسط درجات أفراد عينة البحث على مقياس الأمن النفسي لصالح طلبة السنة الرابعة.
Keywords: قلق الموت -- الأمن النفسي -- طلبة كلية التربية